The Role of Coercive Intellectual Leadership in Improving the Performance of Study Programs Through 6C Characters of Lecturers in Central Java - Ratih Pratiwi; Marno Nugroho; Heri Prabowo; Nanang Yusroni (International Journal of Social Science and Business, 2022)
The facts show that the performance of the Study Program has not been achieved optimally. It can be seen from the accreditation results, quality of learning, scientific publications, and collaboration between institutions. Some study programs still have a low accreditation score (C), even regarding adequate resources. This study aims to analyze the effect of Communication, Collaboration, Compassion, Critical Thinking, Creative Thinking, and Computational Logic in improving the quality of graduation on organizational performance with the Coercive Intellectual Leadership approach. The census technique determined the research sample, meaning that the entire population was used as a sample. This study involved 21 Faculties of Economics and Business in Private Universities in Semarang, Central Java. Data analysis using statistical analysis software SEM-PLS. This research results show that 6C Management has a positive and significant effect on performance. From the data analysis results, coercive intellectual leadership inevitably moderates the effects of collaboration, critical thinking, and logic on performance. However, it cannot affect creativity, communication patterns, and compassion in improving performance.